Neural Correlates of Single- and Dual-Task Walking in the Real World - Pizzamiglio, Sara; Naeem, Usman; Abdalla, Hassan; Turner, Duncan L. (Frontiers in Human Neuroscience, 2017)
Recent developments in mobile brain-body imaging (MoBI) technologies have enabled studies of human locomotion where subjects are able to move freely in more ecologically valid scenarios. In this study, MoBI was employed to describe the behavioural and neurophysiological aspects of three different commonly occurring walking conditions in healthy adults. The experimental conditions were self-paced walking, walking while conversing with a friend and lastly walking while texting with a smartphone. We hypothesised that gait performance would decrease with increased cognitive demands and that condition-specific neural activation would involve condition-specific brain areas. Gait kinematics and high density electroencephalography were recorded whilst walking around a university campus. Conditions with dual tasks were accompanied by decreased gait performance. Walking while conversing was associated with an increase of theta () and beta (β) neural power in electrodes located over left-frontal and right parietal regions, whereas walking while texting was associated with a decrease of β neural power in a cluster of electrodes over the frontal-premotor and sensorimotor cortices when compared to walking whilst conversing. In conclusion, the behavioural ‘signatures’ of common real-life activities performed outside the laboratory environment were accompanied by differing frequency-specific neural ‘biomarkers’. The current findings encourage the study of the neural biomarkers of disrupted gait control in neurologically impaired patients.